Identification of Pathogens and Laboratory Activity Test of Kiwifruit Rot Disease in Guizhou Province, China - Tao Wang; Yanling Ren; Jinyu Zhao; Yingjie Jiang; Jian Tang; Yao Liu; Chao Liu; Juan Wang; Xiaolei Ji; Mingyan Wang (Journal of Chemistry)
Kiwifruit (Actinidia spp.) postharvest decay is common in China, which can cause serious economic losses to kiwifruit industry. In order to further clarify the pathogen of kiwifruit rot disease in Guizhou Province, the rotten fruits of kiwifruit (cultivar “Jinyan”) were collected, and the pathogenic fungi were identified by isolation and purification, pathogenicity test, morphological characteristics, and analysis of rDNA-ITS sequences. The results showed that the pathogenic fungi of kiwifruit rot disease were Diaporthe phaseolorum and Fusarium tricinctum. Meanwhile, the results showed that all the tested agents had a certain inhibitory effect on Diaporthe phaseolorum and Fusarium tricinctum. Among them, 33.5% quinolone SC had the best inhibitory effect on Diaporthe phaseolorum with an EC50 value of 9.67 mg/L, and 25% fludioxonil SC had the best inhibitory effect on Fusarium tridentatus with the EC50 value of 13.13 mg/L. The results will provide a reference for the control of kiwifruit rot disease.